2022
DOI: 10.3390/polym14051031
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Encapsulation by Ionic Gelation Technique of Cryoconcentrated Solution: A Response Surface Methodology and Evaluation of Physicochemical Characteristics Study

Abstract: The objective of this study was to evaluate the optimal conditions to encapsulate cryoconcentrate solutions via ionic gelation technique. Hydrogel beads were prepared using alginate (1%, 2% and 3% (w/w)) and cornstarch (0.5%, 1% and 2% (w/w)). Later, a sucrose/acid gallic solution was concentrated through block freeze concentration (BFC) at three cycles. Thus, each solution was a mixture with the respective combination of alginate/cornstarch. The final solution was added drop-wise on a CaCl2 solution, allowing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…Figure 1 shows the EE% of the CSAlg and Alg hydrogel beads filled with initial model solution (IMS), concentrate from cycle 1 (C1), concentrate from cycle 2 (C2), and concentrate from cycle 3 (C3) solutions. In the present study, it is important to mention that our research group studied the encapsulation efficiency of the different concentrations of sucrose/gallic acid solution (called IMS, C1, C2, and C3) and used the best results in terms of concentration of CSAlg (corn starch at 2% (w/w) and sodium alginate at 2% (w/w)) from a previous study [20]; in addition, we added only sodium alginate (2% w/w) as control (Alg) (the procedure is indicated in Section 4.4). Through this method, the results revealed statistically significant differences between each concentrated solution (IMS vs. C1 vs. C2 vs. C3) and materials (CSAlg vs. Alg) to encapsulate the solutions.…”
Section: Ee%mentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1 shows the EE% of the CSAlg and Alg hydrogel beads filled with initial model solution (IMS), concentrate from cycle 1 (C1), concentrate from cycle 2 (C2), and concentrate from cycle 3 (C3) solutions. In the present study, it is important to mention that our research group studied the encapsulation efficiency of the different concentrations of sucrose/gallic acid solution (called IMS, C1, C2, and C3) and used the best results in terms of concentration of CSAlg (corn starch at 2% (w/w) and sodium alginate at 2% (w/w)) from a previous study [20]; in addition, we added only sodium alginate (2% w/w) as control (Alg) (the procedure is indicated in Section 4.4). Through this method, the results revealed statistically significant differences between each concentrated solution (IMS vs. C1 vs. C2 vs. C3) and materials (CSAlg vs. Alg) to encapsulate the solutions.…”
Section: Ee%mentioning
confidence: 99%
“…Various studies have shown the beneficial effect of encapsulation using calcium alginate hydrogel beads in the protection of bioactive compounds, for example, polyphenols from chokeberry extracts [15], anthocyanins from hibiscus extracts (the beads were added to a yogurt sample, obtaining a high sensory perception) [16], stevia extracts [17], olive leaf extracts [18], and Moringa oleifera extract [19], among others. In the same way, in the last year, our group has successfully explored the potential to form stable calcium alginate hydrogel beads filled with model solution (mix of sucrose and gallic acid) obtained by block FC (BFC), where loading capacity, particles size, shape, water activity, moisture content, and bulk density were studied [20]. Nevertheless, there is still a significant research gap, and future innovative studies on the rheological and thermal behaviors, among other interesting properties, and post-encapsulation of concentrated solutions acquired by BFC are required to obtain scientific knowledge that makes it possible to predict the kinetics of release of polyphenols encapsulated under simulated digestion conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From previous studies on centrifugation‐assisted BFC (Casas‐Forero, Moreno‐Osorio, et al., 2021; Guerra‐Valle et al., 2022; Orellana‐Palma et al., 2021), the present work considers the application of this technology at a first moment. Subsequently, as performed by Dantas et al.…”
Section: Introductionmentioning
confidence: 99%
“…From previous studies on centrifugation-assisted BFC (Casas-Forero, Moreno-Osorio, et al, 2021;Guerra-Valle et al, 2022;Orellana-Palma et al, 2021), the present work considers the application of this technology at a first moment. Subsequently, as performed by Dantas et al (2021), an ice fraction was subjected to the vacuumassisted BFC aiming for better utilization of the nutrients retained in this portion.…”
Section: Introductionmentioning
confidence: 99%